Human-robot interaction for object transfer - Almeida, Luís Miguel Martins (2018)
Robots come into physical contact with humans under a variety of circumstances to perform useful work. This thesis has the ambitious aim of contriving a solution that leads to a simple case of physical human-robot interaction, an object transfer task. Firstly, this work presents a review of the current research within the field of Human-Robot Interaction, where two approaches are distinguished, but simultaneously required: a pre-contact approximation and an interaction by contact. Further, to achieve the proposed objectives, this dissertation addresses a possible answer to three major problems: (1) The robot control to perform the inherent movements of the transfer assignment, (2) the human-robot pre interaction and (3) the interaction by contact. The capabilities of a 3D sensor and force/tactile sensors are explored in order to prepare the robot to handover an object and to control the robot gripper actions, correspondingly. The complete software development is supported by the Robot Operating System (ROS) framework. Finally, some experimental tests are conducted to validate the proposed solutions and to evaluate the system's performance. A possible transfer task is achieved, even if some refinements, improvements and extensions are required to improve the solution performance and range.